ERS International Congress, Madrid, 2019: highlights from the Paediatric Assembly. Issue 2 (20th July 2020) - Nenna, Raffaella; Slaats, Monique; Ersu, Refika; Lo, David; Seglani, Sejal; Nissenbaum, Claire; Horsley, Alex R.; Proesmans, Marijke; Petrarca, Laura; Williams, Emma; Dassios, Theodore; Ardura-Garcia, Cristina; et al.
In this article, the Group Chairs and the Early Career Members of the Paediatric Assembly of the European Respiratory Society (ERS) highlight some of the most interesting findings in the field of paediatrics presented at the 2019 ERS International Congress, which was held in Madrid, Spain. The main findings from each group are summarised at the end of each chapter. Key paediatric messages from the 2019 #ERSCongress https://bit.ly/2XA8UJB